School Road Safety Assessment in Nepal: A Case Study Using SR4S Ratings - Pokhrel, Asmita; Luitel, Sanjay; Tiwari, Hemant (International Journal on Engineering Technology, 2025)
Road Safety has been a concerning issue in the world. The number of road traffic fatalities is escalating, especially in Low-Middle income countries and among the age group of people between 5-29. The case has been similar in Nepal as well. Children are particularly more at risk in Nepalese road due to the lack of road safety furniture on roads more specifically around the school areas. Most Children are forced to navigate their ways to school using roads with no road safety infrastructures like speed limit, speed calming devices, pedestrian crossways etc. In this study, Star Rating for School (SR4S) application was used to assess the road safety condition of a public school based on Nuwakot district of Nepal. The school facilitates more than 1300 students and is very near to the Pasang Lhamu highway. The data collected through the survey for the checklist provided by SR4S tool, was coded in the application and the rating was accessed. Interventions were suggested and implemented by school’s administration and was again accessed for rating.